Determination of Beta Thalassemia trait and abnormal Hemoglobin variant frequency - Miraç Seher Helvacı; Melih Tekinay; Okan Yılmaz; Mustafa Şahin; Öngen İpek; Eren Vurgun; Okan Dikker; Hüseyin Dağ (Iberoamerican Journal of Medicine)
Introduction: Hemoglobinopathies are among the most common hereditary disorders globally, classified into thalassemias and abnormal hemoglobins. Abnormal hemoglobins arise from genetic alterations like point mutations, insertions, or deletions, with Hb S, Hb D, Hb C, and Hb E being the most prevalent in Turkey. Beta-thalassemia minor is characterized by reduced or absent synthesis of one beta-globin chain. High-performance liquid chromatography (HPLC) is widely used for screening, while genetic methods remain the gold standard for definitive diagnosis. The estimated frequency of beta-thalassemia traits in Turkey is 2–3%, and abnormal hemoglobins 0.95%. This study aimed to determine the frequency of beta-thalassemia traits and abnormal hemoglobins in a central laboratory. Material and methods: Retrospective data from hemoglobin variant analyses conducted between November 1, 2020, and July 31, 2024, in the hospital’s central laboratory were collected via the Laboratory Information Management System (LIMS). Samples from patients aged 6 months to 99 years were included. Repeated samples and those from infants under 6 months (with high HbF) were excluded. Frequencies of Hb S, D, C, and E were calculated as a percentage of total tested samples. HbA2 > 3.5% was used to identify beta-thalassemia traits. Analyses were performed using a cation-exchange HPLC-based Adams HA-8180T system. Results: A total of 223,609 samples were analyzed. Abnormal hemoglobins were found in 0.35% (800 cases): Hb S (0.15%), Hb D (0.13%), Hb C (0.05%), and Hb E (0.01%). Beta-thalassemia traits (HbA2 ≥ 3.6%) were found in 6,017 cases (2.69%). Conclusions: Hb S was the most frequent abnormal variant. The frequency of abnormal hemoglobins was lower than literature reports, while beta-thalassemia traits matched reported rates. HPLC is valuable for screening, but genetic testing remains essential for definitive diagnosis. These findings contribute to better prediction of hemoglobinopathy prevalence.